2017
DOI: 10.1186/s12951-017-0305-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond enhances immune responses in mice against recombinant HA/H7N9 protein

Abstract: BackgroundThe continuing spread of the newly emerged H7N9 virus among poultry in China, as well as the possibility of human-to-human transmission, has attracted numerous efforts to develop an effective vaccine against H7N9. The use of nanoparticles in vaccinology is inspired by the fact that most pathogens have a dimension within the nano-size range and therefore can be processed efficiently by the immune system, which leads to a potent immune response. Herein, we report a facile approach to increase antigen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 30 publications
(46 reference statements)
2
41
0
Order By: Relevance
“…To express the recombinant protein in planta, the agroinfiltration protocol was performed as described by Pham et al (29), with some modifications. Briefly, bacteria containing the expression vector pCB301-COE-GCN4pII-cmyc-his-KDEL and plant vector including HcPro (23), that was used as a gene silencing suppressor for enhancing the expression levels of targeting proteins in plants (30,31), were mixed and diluted in an infiltration buffer [ Recombinant COE-GCN4pII protein was purified via immobilized metal affinity chromatography (IMAC) as described by Pham et al (29). The oligomeric form of purified COE-GCN4pII protein was determined by a cross-linking reaction that was described by Weldon et al (32) and a native PAGE.…”
Section: Production and Characterization Of Plant-based Recombinant Pmentioning
confidence: 99%
“…To express the recombinant protein in planta, the agroinfiltration protocol was performed as described by Pham et al (29), with some modifications. Briefly, bacteria containing the expression vector pCB301-COE-GCN4pII-cmyc-his-KDEL and plant vector including HcPro (23), that was used as a gene silencing suppressor for enhancing the expression levels of targeting proteins in plants (30,31), were mixed and diluted in an infiltration buffer [ Recombinant COE-GCN4pII protein was purified via immobilized metal affinity chromatography (IMAC) as described by Pham et al (29). The oligomeric form of purified COE-GCN4pII protein was determined by a cross-linking reaction that was described by Weldon et al (32) and a native PAGE.…”
Section: Production and Characterization Of Plant-based Recombinant Pmentioning
confidence: 99%
“…13 NDP are also being extensively studied as carriers of pharmacological agents for delivery of cytotoxic chemicals into drug-resistant tumors. [14][15][16][17] Furthermore, new frontiers were recently broached that demonstrate potential medical application in immune enhancement (vaccine), 18,19 adjuvant, 20 and genetic neurological conditions. 21 Pharmacokinetic (PK) advantages gained by the co-junction of tumor-toxic compounds to NDP have shown preservation of efficacy while reducing the compounds' toxicity by restriction of the dosing regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Hemagglutinin trimer has also been exploited as a potential antigen for inducing protective immunity against influenza virus. Pham et al, immunized BALB/C mice with nanodiamond conjugated trimeric H7 and observed a significant higher H7 specific IgG production as compared to immunization with H7 trimeric antigen alone [151] . Similarly, Ross et al, have shown that intranasal or subcutaneous immunization of BALB/c mice with polyanhydride nanoparticles encapsulated H53 induced high titer neutralizing antibodies.…”
Section: Nanovaccines For Influenzamentioning
confidence: 99%